2017
DOI: 10.1002/1873-3468.12584
|View full text |Cite
|
Sign up to set email alerts
|

Molecular basis for TANK recognition by TRAF1 revealed by the crystal structure of TRAF1/TANK complex

Abstract: Coordinate and structural factor were deposited in the Protein Data Bank under PDB ID code 5H10.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 41 publications
1
15
0
Order By: Relevance
“…Size-exclusion chromatography showed that both TRAF-N domains eluted at approximately 17 mL, indicating the formation of a trimer in solution (Figure 2D,E). These results agree with those of previous structural and biochemical studies [20,21]. Using purified protein samples of the TRAF-N domain of TRAF1 and TRAF2, we initially performed Native PAGE to analyze the trimeric homogeneity and compactness.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Size-exclusion chromatography showed that both TRAF-N domains eluted at approximately 17 mL, indicating the formation of a trimer in solution (Figure 2D,E). These results agree with those of previous structural and biochemical studies [20,21]. Using purified protein samples of the TRAF-N domain of TRAF1 and TRAF2, we initially performed Native PAGE to analyze the trimeric homogeneity and compactness.…”
Section: Resultssupporting
confidence: 89%
“…Based on previous structural and biochemical studies of the TRAF1 TRAF domain, the TRAF-N domain is critical for trimer stabilization of TRAF1 and this trimerization is functionally important [19,20]. To further analyze the contribution of the TRAF-N domain to trimer stabilization with respect to the other TRAF family members including TRAF2, we performed various characterization assays with the TRAF domains of TRAF2 and TRAF4.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the structural similarity of the TRAF domain within the TRAF family, each domain of each TRAF protein is specific to interacting upstream receptors. In this review, we summarized the current understanding of TRAF-binding motifs of many receptors by examining the structures of all six TRAF family members and complexes of each TRAF with various receptors including recently characterized complexes TRAF4–GPIb (32), TRAF1–TANK (37), TRAF3–Cardif (27), and TRAF6–MAVS (39). Because the sequences of binding hot spots are conserved in TRAF1, −2, −3, and −5, they share the same binding consensus motifs, namely, one major motif, Px(Q/E)E, and two minor motifs: Px(Q/E)xxD, and Px(Q/E)xT.…”
Section: Discussionmentioning
confidence: 99%
“…In the Px(Q/E)xxD motif, the side chains of the residues at positions P −2 , P 0 , and P 3 are critical for the TRAF interaction, unlike the major binding motif, where the side chains of residues at positions P −2 , P 0 , and P 1 participate in the interaction (Figure 2C). Several modified interactions involving the minor motif have been reported in structural studies on TRAF3 in complex with various receptors, including CD40 (26), LMP1 (36), and TANK (35) and the most recently solved TRAF1–TANK complex (37). In this case, the side chains of the P −2 , P 0 , and P 2 positions are involved in the TRAF interaction.…”
Section: Receptor Recognition By Trafsmentioning
confidence: 99%
See 1 more Smart Citation